Prediction of Class II improvement after rapid maxillary expansion in early mixed dentition - Alberto Caprioglio; Chiara Bergamini; Lorenzo Franchi; Nicolò Vercellini; Piero Antonio Zecca; Riccardo Nucera; Rosamaria Fastuca (SpringerOpen, 2017)
Abstract Background The aim of this study is to identify cephalometric pretreatment parameters for prediction of Class II improvement induced by rapid maxillary expansion. Methods Lateral cephalograms of 30 patients (mean age 8.3 ± 1.6 years old) showing Class II molar relationship and undergone to rapid maxillary expansion on the upper deciduous molars were traced before treatment, and molar relation changes were evaluated on dental casts before and after treatment. Overall treatment time lasted 10.2 ± 2 months. Good responders (18 subjects, 10 females and 8 males) showed improvement of at least 2.50 mm, and bad responders (12 subjects, 7 females and 5 males) showed no improvement, improvement less than 2.50 mm, or worsening of molar relationship after treatment. Student's t test was used to assess significance of differences between groups, and discriminant analysis allowed identification of predictive pretreatment variables. Results Articular angle, superior gonial angle, and mandibular dimensions (Co-Gn, S-Ar, Ar-Go, Go-Me) showed significant differences in the comparison between groups. Mandibular length Co-Gn and superior gonial angle were selected as significant predictive variable for discrimination. Conclusions Patients with smaller mandibular length and more acute superior gonial angle are expected to have more chances to improve molar Class II after rapid maxillary expansion.